2012
DOI: 10.1681/asn.2011121144
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-324-3p Promotes Renal Fibrosis and Is a Target of ACE Inhibition

Abstract: The contribution of microRNA (miRNA) to the pathogenesis of renal fibrosis is not well understood. Here, we investigated whether miRNA modulates the fibrotic process in Munich Wistar Fromter (MWF) rats, which develop spontaneous progressive nephropathy. We analyzed the expression profile of miRNA in microdissected glomeruli and found that miR-324-3p was the most upregulated. In situ hybridization localized miR-324-3p to glomerular podocytes, parietal cells of Bowman's capsule, and most abundantly, cortical tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 42 publications
(45 reference statements)
4
72
0
Order By: Relevance
“…14 Several miRs have been reported to suppress transcription of important mRNAs that regulate the development of renal fibrosis. [15][16][17][18][19][20][21][22][23][24] However, few studies have focused on the effects of exogenous miR delivery on renal fibrosis in an in vivo therapeutic setting. [15][16][17][18]24 miR146a has been reported to inhibit inflammation by suppressing target mRNAs, such as those encoding tumor necrosis factor receptor-associated factor 6 (TRAF6), interleukin-1 receptor-associated kinase 1 (IRAK1), and Toll-like receptor 4 (TLR4), resulting in the inhibition of NF-κB in several organs.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several miRs have been reported to suppress transcription of important mRNAs that regulate the development of renal fibrosis. [15][16][17][18][19][20][21][22][23][24] However, few studies have focused on the effects of exogenous miR delivery on renal fibrosis in an in vivo therapeutic setting. [15][16][17][18]24 miR146a has been reported to inhibit inflammation by suppressing target mRNAs, such as those encoding tumor necrosis factor receptor-associated factor 6 (TRAF6), interleukin-1 receptor-associated kinase 1 (IRAK1), and Toll-like receptor 4 (TLR4), resulting in the inhibition of NF-κB in several organs.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-324-3p increased proximal tubular cell (PTC) susceptibility to developing a fibrogenic phenotype in response to TGF-b. 15 In the study by Zhou et al, renal miR-150 expression correlated with the expression of profibrotic molecules like collagen I (COL1), which were significantly increased in the renal tubulointerstitium. Whether the altered expression of miR-150 in LN patients was associated with changes in clinical markers such as proteinuria was not shown, possibly because kidney specimens were retrieved from LN patients enrolled between 1976 and 1999 and no clinical data were available.…”
mentioning
confidence: 99%
“…Treatment of the rats with an ACE inhibitor, lisinopril, significantly raised urine and plasma concentrations of Ac-SDKP and suppressed interstitial collagen deposition in the kidneys with higher Prep expression and less miR-324-3p expression in the tubular epithelia. 15 This study strongly suggests that dysregulation of the miR-324-3p/Prep complex contributes to the progression of spontaneous nephropathy in MWF rats. However, its universal validity remains to be clarified, because miR-324-3p has never been identified in any lists of upregulated miRNAs detected in kidney tissues from either diabetic nephropathy or IgA nephropathy, 14,21,22 in which the profibrotic effects of ACE inhibition have been confirmed.…”
mentioning
confidence: 64%
“…20 Delivery of a miR-324-3p mimic into cultured tubular epithelial cells resulted in significant downregulation of mRNA encoding Prep and protein expression and suppressed TGF-b1 induction of a profibrotic marker, a-smooth muscle actin, in those cells. 15 In situ hybridization and immunohistochemistry also demonstrated that upregulation of miR-324-3p expression associates with reduced expression of Prep in both glomeruli and cortical tubular epithelia in fibrotic areas. Treatment of the rats with an ACE inhibitor, lisinopril, significantly raised urine and plasma concentrations of Ac-SDKP and suppressed interstitial collagen deposition in the kidneys with higher Prep expression and less miR-324-3p expression in the tubular epithelia.…”
mentioning
confidence: 90%
See 1 more Smart Citation